Manajemen Investasi dan Perencanaan Dana Pensiun Pada Bapak Sunli - , Jemmy Dwi Putra, Prof. Dr. Tandelilin Eduardus, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis is a case study on wealth management categorized by High Net worth Individuals by identifying the profile of client based on type of risk taking, analyze and evaluate investment management, analyze and evaluate the need for pension funds and make recommendations to client based on pillars in the Wealth Management. In this case, the client called Mr. Sunli who has limitations in wealth management due to lack of knowledge and expertise of the investment instruments and lack of time. Client is businessman and now 55 years old with moderate risk tolerance level. Based on the financial goals to be achieved by the client that is increasing the wealth and maintain living standards after retirement. The author recommends three alternative scenarios to the client that refers to the two pillars of Wealth Management which are Wealth Accumulation and Growth and Wealth Distribution and Transition. Based on the three scenarios are recommended to the client then the client decides to choose the second scenario. Projection of existing client accounts over the next year to be Rp.40.379.633.600, 00 or an increase of Rp.4.772.337.600, 00 and the proposed projection accounts (scenario two) during the next year to be Rp.42.920.963.600, 00 or an increase of Rp.7.313.667.600,00.